PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PADA BENGKEL AHASS PATI - Ari Setiawan, 08.05.51.0144 Bayu; kunartinah, Kunartinah (Students Journal of Economic and Management, 2012)
This research was based the existence of complaints or customer dissatisfaction over the services provided bengkel PT. Astra International Tbk Honda Sales Office Pati. Complaints should be addressed properly by the partiesbengkel PT. Astra International Tbk Honda Sales Office Pati, because if not addressed properly, then the customer will tell a disappointing experience to others, so that will worsen the image and the existence of the workshop. Complaints can be minimized by taking the necessary steps, so customers will feel satisfied with the services and support provided by the workshop. Customer satisfaction in the long term to create customer loyalty towards bengkel PT. Astra International Tbk Honda Sales Office Pati. The purpose of this study wa to analyze the impact of service quality, including physical evidence, reliability, responsiveness, assurance and empathy towards customer satisfaction bengkel PT. Astra International Tbk Honda Sales Office Pati. This research was conducted using questionnaires to 100 people bengkel PT. Astra International Tbk Honda Sales Office Patisubscribers obtained by using accidental sampling technique. We then performed an analysis of data obtained in the form of quantitative and qualitative analysis. A quantitative analysis include validity and reliability test, the classic assumption test, multiple regression analysis, Goodness ofFit tests through the F test and t test and coefficient of determination (RÂ²). Qualitative analysis is an interpretation of the data obtained in this study, and results of data processing that have been implemented with a description and explanation. The results showed that the coefficient of determination shown in the Adjusted R Square of 0.542, which means that customer satisfaction can be explained by the five independent variables in this research that physical evidence, reliability, responsiveness, assurance and empathy is 54.2%. The remaining 45.8% can be explained by other variables outside of the five variables used in this study. Partially based on the results of t test variables in this study has positive and significant in which physical evidence has the greatest influence than other variables in this study, whereas responsiveness has the smallest influence on customer satisfaction. F test results indicate that simultaneously or jointly variables in this research that physical evidence, reliability, responsiveness, assurance and empathy have a positive and significant impact on customer satisfaction.Keywords: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy and Customer Satisfaction